Analysis Skills of Early Childhood in The Implementation of Creative Dance Wedcforting - Dhea Ardiyanti; Leli Kurniawati; Heny Djoehaeni (Universitas Negeri Semarang, 2024)
This study aims to reveal analytical skills of early childhood as an indicator of critical thinking skills in the implementation of WEDCFORTING creative dance learning. This research is based on optimizing critical thinking skills in children from an early age through fun learning activities. The method used in this research is descriptive qualitative method so that everything that happens in the field can be described in detail. The research activity was carried out by involving 13 young children at one of the kindergarten institutions in Purwakarta Regency. The results of the research show that children get the opportunity to explore ideas and ideas into a series of dance movements. This shows that analytical skills as an indicator of children's critical thinking abilities are well optimized in the implementation of WEDCFORTING creative dance learning. Thus, WEDCFORTING creative dance learning can be used as a reference in implementing dance learning in early childhood as an effort to optimize critical thinking abilities.